PERAN PENDIDIKAN DAYAH DALAM PEMBENTUKAN KARAKTER PEMUDA ACEH (STUDI KASUS DI ACEH TENGGARA) - Idris, M. Arif (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2020)
In Aceh, the role of Dayah is very important considering its existence is supported by society especially in education. Other problems arise when viewed from the socio-cultural context of society when faced with the diversity present in the midst of society, especially in the border area of ACEH. The existence of Dayah amid the diversity of society consisting of various tribes and religions is certainly a challenge for the existence of Dayah as an institution that provides the character of ACEH youth. This kind of condition happened in southeast Aceh. This article aims to see how the role of education in the form of youth character in Southeast Aceh. This study used a qualitative approach with the subject is the head of Dayah, the Council of Teachers, and the students in the Dayah. The Dayah is randomly selected. Data collection techniques using observation techniques, interviews, and documentation. Then the data is analyzed by using data reduction measures, displays. The results of research show that Dayah in southeast Aceh has an important position in the midst of society. Its existence is supported by the government and community, and one of the districts that have the most Dayah in Aceh. The students graduated from the Dayah felt a difference before studying in the father after studying in the Dayah. In the development Dayah did not experience any meaningful obstacles.